2013
DOI: 10.1017/s0010417513000650
|View full text |Cite
|
Sign up to set email alerts
|

“The army and the people are one hand!” Fraternization and the 25th January Egyptian Revolution

Abstract: On 28 January 2011 the Egyptian army was deployed onto Cairo's streets following three days of escalating protests. Upon entering Midan al-Tahrir, a column of newly arriving army tanks and APCs was attacked by protestors. Throwing stones and dousing the vehicles in petrol before setting them alight, protestors pulled soldiers out of their vehicles and beat them. Seizing ammunition and supplies, protestors even commandeered a tank. Minutes later those same protestors were chanting pro-army slogans, posing for p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(20 citation statements)
references
References 28 publications
0
18
0
2
Order By: Relevance
“…yes, we hated them, but then you get sympathy for them and then you go back to fight, that's how it goes." 57 While the degree of fraternization between protesters and security forces was not as outspoken as other studies have found of Egypt, 58 it is clear that the Tunisian population, including security forces, carved out spaces for building unity, even if it was as modest as shared meals during lulls in the fighting.…”
Section: Successful Regime Change In Tunisiamentioning
confidence: 90%
“…yes, we hated them, but then you get sympathy for them and then you go back to fight, that's how it goes." 57 While the degree of fraternization between protesters and security forces was not as outspoken as other studies have found of Egypt, 58 it is clear that the Tunisian population, including security forces, carved out spaces for building unity, even if it was as modest as shared meals during lulls in the fighting.…”
Section: Successful Regime Change In Tunisiamentioning
confidence: 90%
“…I argue that the expats in the security forces pose a great challenge to the protesters, as they often cannot understand each other's languages and cultural norms. Ketchley (2014) has described how tactics of fraternization were part of what generated the bond between protesters and Egypt's army. Such tactics are challenged in Bahrain due to cultural and linguistic barriers.…”
Section: The Composition Of the Military As A Challenge For Nonviolenmentioning
confidence: 99%
“…36 More recently, Ketchley has argued that fraternization between Egyptian military personnel and protestors changed soldiers' impressions of Arab Spring demonstrations over time and made them less willing to use force against civilians. 37 Such accounts show the power of persuasion when soldiers are deployed against their own populations. Yet, existing arguments focus on a particular persuasion equation: that flowing from demonstrator to soldier.…”
Section: Strong Ties Persuasion and Coordinated Actionmentioning
confidence: 99%